Real-time detection method and system for identifying individual aerosol particles (2004)
An improved method and system of identifying individual aerosol particles in real time. Sample aerosol particles are collimated, tracked, and screened to determine which ones qualify for mass spectrometric analysis based on predetermined qualification or selection criteria. Screening techniques include one or more of determining particle size, shape, symmetry, and fluorescence. Only qualifying particles passing all screening criteria are subject to desorption/ionization and single particle mass spectrometry to produce corresponding test spectra, which is used to determine the identities of each of the qualifying aerosol particles by comparing the test spectra against predetermined spectra for known particle types. In this manner, activation cycling of a particle ablation laser of a single particle mass spectrometer is reduced.